Meat allergy associated with galactosyl‐α‐(1, 3)‐galactose (α‐Gal)—Closing diagnostic gaps by anti‐α‐Gal IgE immune profiling. Issue 1 (15th August 2017) - Jappe, U.; Minge, S.; Kreft, B.; Ludwig, A.; Przybilla, B.; Walker, A.; Varga, R.; Seidel, P.; Biedermann, T.; Anemüller, W.; Kromminga, A.; Ruëff, F.; et al.
Abstract: Background: Glycoproteins and glycolipids of some mammalian species contain the disaccharide galactosyl‐α‐(1, 3)‐galactose (α‐Gal). It is known that α‐Gal is immunogenic in humans and causes glycan‐specific IgG and also IgE responses with clinical relevance. α‐Gal is part of the IgE‐reactive monoclonal therapeutic antibody cetuximab (CTX) and is associated with delayed anaphylaxis to red meat. In this study, different α‐Gal‐containing analytes are examined in singleplex and multiplex assays to resolve individual sensitization patterns with IgE against α‐Gal. Methods: Three serum groups, α‐Gal‐associated meat allergy (MA) patients, idiopathic anaphylaxis (IA) patients with suspected MA, and non‐meat‐allergic healthy control individuals (HC), were analyzed via singleplex allergy diagnostics and a newly established immunoblot diagnostic system. The new dot blot detection system resolved individual IgE sensitization profiles for α‐Gal‐containing analytes CTX, bovine thyroglobulin (Bos d TG), and human serum albumin ( HSA)‐conjugated α‐Gal. Results: Singleplex allergy diagnostics using the α‐Gal analytes CTX and Bos d TG confirms the history of MA patients in 91% and 88% of the cases, respectively. A novel dot blot‐based assay system for the detection of IgE against α‐Gal reveals individual IgE sensitization profiles for α‐Gal‐containing analytes. An α‐Gal‐associated IgE cross‐reactivity profile (IgE against CTX, Bos d TG, and HSA‐α‐Gal) was identified, which is associated with MA. Conclusions: Detection of individual sensitization patterns with different α‐Gal‐containing analytes provides the basis for an individual allergy diagnosis for α‐Gal‐sensitized patients. Higher amounts of α‐Gal in pork and beef innards compared to muscle meat as indicated by a higher staining intensity are a plausible explanation for the difference in allergic symptom severity.